Cultura de segurança do paciente: avaliação de enfermeiros* - Silvana Pagani; Karla Crozeta; Alexandra Berndt Razeira Crisigiovanni (Universidade Federal do Ceará, 2019)
Objective to evaluate the safety culture of the teaching hospital patient.Methods evaluative research, with 68 nurses, whose instrument used was the Safety Attitudes Questionnaire - Short Form adapted, composed of questions covering six domains.Results the best evaluation was of the Satisfaction at Work domain, with an average of 88.48, the only one positively classified. The domain that measures the Perception of Management of the Unit and the Hospital obtained smaller evaluations, with averages 61.1 and 59.6, respectively.Conclusion nursing professionals expressed satisfaction with the work; however, considering that only one domain had a positive result, the safety culture of the hospital patient presents weaknesses from the perspective of the participating nurses.